Regenerated graphite active material and preparation and application thereof

Through the gas and liquid treatment and the combined process of additives, the shortcomings in consistency and conductivity of waste graphite recycled materials are solved, and the preparation of recycled graphite materials with high purity and excellent performance is achieved, and the battery without conductivity is realized is realized. Fast charging and long cycle stability.

CN119118121AActive Publication Date: 2024-12-13CENT SOUTH UNIV

Patent Information

Application Number
CN202411278863.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-13
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

There is room for improvement in existing waste graphite recycled materials in terms of product consistency, raw material compatibility, electrical conductivity, etc., and external conductive agent is usually required when assembling batteries, which affects the first-circle coulomb efficiency, energy density and high-magnification long-cycle performance of the battery.

Method used

The two-stage treatment methods of gas and liquid are combined with the combined treatment of functional gas and solute components, combined with auxiliary agents and negative pressure heat treatment, so as to achieve the preparation of recycled graphite materials without auxiliary conductive agents, and optimize the purification effect and electrochemical performance of graphite.

Benefits of technology

Recycled graphite material with a purity of more than 99.99% was obtained, and batteries with excellent head effect, fast charging and long cycle stability can be assembled without the assistance of conductive agent, thereby improving the efficiency and value of the regeneration process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118121A_ABST
    Figure CN119118121A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of waste graphite regeneration, and particularly relates to a preparation method of a regenerated graphite active material, which comprises the following steps: carrying out first-stage gas-solid treatment on waste graphite powder in an atmosphere A in advance to obtain a first-stage material; the first-stage material is placed in an aqueous solution containing a solute a and a solute b for second-stage solvent heat treatment, and a second-stage material is obtained through separation; and mixing the second-stage material, an auxiliary agent and a carbon source, carrying out negative pressure heat treatment at the temperature T1, cooling to the temperature T2, directly contacting with a cooling medium, and carrying out cold quenching treatment to obtain the regenerated graphite active material. The invention also comprises the material prepared by the preparation method and application of the material in a battery. The graphite material regenerated by the method disclosed by the invention has excellent quick charge and long cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste graphite regeneration, and in particular to a method for regenerating waste graphite into negative electrode material for lithium ion batteries. Background Art

[0002] Graphite has a wide range of applications in the fields of electrical, metallurgical, national defense, new energy, and chemical industries due to its stable chemical properties, high temperature resistance, corrosion resistance, high conductivity, and easy processing. The graphite involved in the above fields is mainly divided into artificial graphite and natural graphite. Artificial graphite needs to be selected and purified in the early stage, and natural graphite needs to be graphitized at high temperature. Therefore, from the perspective of resource recycling and environmental protection, the recycling of waste graphite is of great significance.

[0003] For the recycling of waste graphite, the main means are acid treatment, alkali treatment, carbon coating, etc. For example, the Chinese patent document with publication number CN118486939A discloses a carbon-coated graphite material and a preparation method thereof using the negative electrode material and diaphragm in waste batteries as raw materials, and specifically records the treatment scheme of washing, acid washing, centrifugal washing, drying and pre-calcining the graphite negative electrode sheet, and then sieving. For another example, the Chinese patent document with publication number CN118198570A discloses a high-rate regenerated graphite negative electrode material and a preparation method thereof, and specifically discloses the scheme of washing the waste graphite negative electrode sheet with dimethyl carbonate and purifying it by medium-high temperature roasting.

[0004] In summary, although there are many methods for recycling waste graphite in the existing technology, there is still room for improvement in the product consistency, raw material compatibility, conductivity, etc. of the existing recycled materials. In addition, external conductive agents are usually required when assembling batteries. The battery's first-cycle coulombic efficiency, energy density, lithium source loss, and high-rate long-cycle performance still have room for improvement. Summary of the invention

[0005] In view of the problems faced by existing waste graphite recycled materials, the first purpose of the present invention is to provide a method for preparing recycled graphite active materials, aiming to prepare recycled graphite materials with good consistency and excellent coulombic efficiency, energy density and high-rate long cycle performance without the need for auxiliary conductive agents.

[0006] The second purpose of the present invention is to provide a regenerated graphite active material obtained by the preparation method and its application in lithium ion batteries.

[0007] The third object of the present invention is to provide a lithium ion battery comprising the regenerated graphite active material and a negative electrode and a negative electrode material thereof.

[0008] In the conventional electrode manufacturing process, it is necessary to add 2-5% of highly conductive carbon materials such as conductive carbon black or carbon nanotubes. This part of additives generally has a high production cost (such as carbon nanotubes), and the addition of conductive carbon will reduce the proportion of active substances and affect the energy density of the battery; in addition, the addition of conductive carbon in the electrode will make it difficult to recycle graphite from waste batteries, and a certain process is required to remove the conductive carbon to improve the purity of the recycled graphite. Therefore, through a lot of research, the present invention provides the following preparation process for regenerated graphite materials that can obtain excellent performance without auxiliary conductive agents, as follows:

[0009] A method for preparing a regenerated graphite active material, comprising the steps of:

[0010] Step (1): Gas and liquid two-stage processing

[0011] The waste graphite powder is subjected to a first stage of gas-solid treatment in atmosphere A to obtain a first stage of material; the first stage of material is then placed in an aqueous solution containing solute a and solute b for a second stage of solvent thermal treatment to separate and obtain two stages of material;

[0012] The atmosphere A contains at least one functional gas selected from oxygen, carbon dioxide and ammonia; the temperature of the first gas-solid treatment is 350-600°C;

[0013] Solute a is the solute that can ionize into H + The solute b comprises ferrite;

[0014] Step (2):

[0015] The second-stage material, the additive and the carbon source are mixed and subjected to negative pressure heat treatment at temperature T1, and then cooled to temperature T2 and directly contacted with a cooling medium for cold quenching to obtain the regenerated graphite active material;

[0016] The auxiliary agent is one or more of cobalt acetylacetonate, nickel acetylacetonate, cobalt naphthenate, nickel naphthenate, cobalt acetate, nickel acetate, dicobalt octacarbonyl, cobalt oxalate, nickel oxalate, and nickel benzoate;

[0017] The temperature T1 is above 700°C, and the temperature T2 is between 300 and 600°C.

[0018] The present invention innovatively subjects the waste graphite to the gas and liquid two-stage treatment in advance, and further coordinates the atmosphere in the gas-solid treatment stage, the solute components in the liquid phase treatment stage, and the combination of negative pressure heat treatment and cold quenching process assisted by additives. This can improve the purification effect of graphite, and can obtain a recycled graphite material with a purity of more than 99.99% and excellent performance. For example, the recycled graphite material described in the present invention can be assembled without the assistance of a conductive agent to obtain a battery with excellent first efficiency, fast charging, and long cycle stability.

[0019] In the present invention, the waste graphite powder is waste batteries, waste graphite crucibles, waste graphite electrodes, and waste graphite generated by the semi-conductive industry and the smelting industry.

[0020] In the present invention, in order to improve the efficiency and value of the regeneration process, the graphitization degree of the waste graphite powder can be above 82%, and the fixed carbon content can be above 80%.

[0021] In the present invention, the particle size of the waste graphite powder can be pre-controlled to be between D50=3 and 18 μm.

[0022] In the present invention, the waste graphite powder is subjected to the gas phase treatment in advance, and then the liquid phase treatment is carried out, and the conditions of the gas phase-liquid phase treatment are further coordinated and controlled. This can significantly optimize the surface and interlayer physical and chemical characteristics of the graphite, and then combine with subsequent processes to improve the electrochemical properties of the regenerated graphite in the absence of a conductive agent, especially the long cycle performance under fast charging and high rate.

[0023] In the present invention, the functional gas in the atmosphere A is oxygen, and its content is 10-40v%, and it can further be air. The functional gas is carbon dioxide, and its content is 5-20v%. The functional gas is ammonia, and its content is 2-8v%.

[0024] In the atmosphere A, the functional gas is a mixed gas of oxygen and ammonia in a volume ratio of 1 to 5:1. The content of the mixed functional gas in the atmosphere A may be 10 to 25%.

[0025] The atmosphere A further comprises a diluent gas, and the diluent gas comprises at least one of air, argon, helium and nitrogen.

[0026] In the present invention, the time of the first gas-solid treatment is 4 to 12 hours, and can further be 5 to 10 hours.

[0027] In the present invention, the solute a includes one or more of hydrochloric acid, sulfuric acid and nitric acid.

[0028] In the solute b, the ferrite includes at least one of sodium ferrite, potassium ferrate, potassium ferrate and zinc ferrite.

[0029] Preferably, the solute b further comprises at least one auxiliary solute b1 selected from ammonium ferric citrate, ammonium ferric sulfate and ferric acetate. Studies have shown that the combination of solute b1 and ferrite can jointly optimize the interlayer and physical and chemical characteristics of the regenerated graphite, and can optimize its fast charging performance.

[0030] Preferably, in the solute b, the solute b1 accounts for 1 to 15% by weight of the ferrite.

[0031] In the present invention, in the aqueous solution, the concentration of the solute a is 0.1-2M, and can further be 0.2-1M; the concentration of the solute b is 0.1-2M, and can further be 0.1-0.5M.

[0032] In the present invention, the aqueous solution may contain a water-soluble organic solvent, preferably at least one of methanol, ethanol, acetone, isopropanol, n-propanol and acetic acid. Studies have shown that the addition of a certain amount of water-soluble organic solvent to the aqueous solvent can further optimize the material's physical and chemical structure, and can further enhance its fast charging and long-cycle stability.

[0033] In the present invention, the liquid-to-solid ratio of the first-stage material and the aqueous solution can be reasonably adjusted according to needs, and can be 5 to 20 mL / g in consideration of cost.

[0034] Preferably, the first-stage material and the aqueous solution are pre-ultrasonicated and then placed in a closed container and heated for the second stage of solvent thermal treatment. In the present invention, the first-stage material is pre-ultrasonicated in the aqueous solution and then further subjected to subsequent solvent thermal treatment, which helps to further strengthen the surface and interlayer structure of the recycled material, and can further enhance its fast charging and long cycle stability.

[0035] The temperature of the second stage solvent thermal treatment is 100°C or higher, and further 100-150°C.

[0036] The time of the second solvent thermal treatment is 4 to 12 hours.

[0037] In the present invention, the additive comprises dicobalt octacarbonyl, and selectively comprises one or more of nickel acetylacetonate, nickel naphthenate, nickel acetate, nickel oxalate, and nickel benzoate. Further, in the additive, the weight content of dicobalt octacarbonyl is 30-60wt.%. Studies have shown that the combination of dicobalt octacarbonyl and nickel components can strengthen the interlayer and surface properties of graphite, and can optimize its rate and long cycle performance.

[0038] In the present invention, the weight ratio of the second-stage material to the auxiliary agent is 100:0.2-5, and can further be 100:1-2.

[0039] In the present invention, the carbon source may be a carbon-containing organic matter known in the industry, for example, it may include one or more of common asphalt, polypropylene, phenolic resin, starch, ethylenediamine, polyethylene glycol, glucose, and sucrose.

[0040] In the present invention, the weight ratio of the second-stage material to the carbon source is 100:5-15, and can further be 100:8-12.

[0041] In the present invention, the second-stage material, the additive, and the carbon source are mixed under liquid phase positive pressure, and then subjected to a desolventizing treatment to obtain a mixture, and the obtained mixture is then subjected to a subsequent negative pressure heat treatment. The present invention also shows that compounding the second-stage material, the additive, and the carbon source under positive pressure in advance can further enhance the combined synergy of the components, help further enhance the physical and chemical characteristics of the surface and interlayers of the recycled material, and further enhance its fast charging and long cycle performance.

[0042] In the present invention, the pressure in the positive pressure mixing stage is above 5 atm (atm refers to standard atmospheric pressure), and can further be 5 to 15 atm.

[0043] In the present invention, the pressure in the negative pressure heat treatment stage may be below 0.5 atm, and may be 1 to 100 Pa in consideration of the equipment cost.

[0044] In the present invention, the temperature of the negative pressure heat treatment may be 1000 to 1400°C, and further may be 1000 to 1200°C.

[0045] Preferably, the negative pressure heat treatment time is 4 to 15 hours, and further can be 6 to 10 hours.

[0046] In the present invention, after the negative pressure heat treatment, the material may be cooled to the temperature T2 by conventional means such as in a furnace.

[0047] In a preferred embodiment of the present invention, after the negative pressure heat treatment is completed, the atmosphere B can be used to assist cooling to a temperature T2. The atmosphere B is one or more of nitrogen, argon, helium, and carbon dioxide. The present invention also shows that the use of the atmosphere B to assist cooling, followed by subsequent cold quenching treatment, can synergistically optimize the surface and interlayer physical and chemical characteristics of the regenerated graphite, and can further enhance its fast charging and long cycle performance.

[0048] In the present invention, the cooling medium is liquid nitrogen, dry ice or water.

[0049] The invention also provides a regenerated graphite active material prepared by the preparation method.

[0050] The preparation method described in the present invention can give the prepared material special physical and chemical characteristics, and the material prepared by the preparation method can be assembled into a negative electrode and a battery without a conductive agent. Not only that, it can also obtain excellent first efficiency, fast charging and long cycle performance at high rate.

[0051] The present invention also provides an application of the regenerated graphite active material prepared by the preparation method, which is used as a negative electrode active material to prepare an alkali metal ion battery.

[0052] In the present invention, the negative electrode active material and the binder are combined to prepare the negative electrode material without an external conductive agent, and the negative electrode material is used for preparing an alkali metal ion battery.

[0053] The present invention also provides a negative electrode of an alkali metal battery, comprising a negative electrode current collector and a negative electrode material composited on the surface thereof, wherein the negative electrode material comprises a negative electrode active material and a binder, wherein the negative electrode active material comprises the regenerated graphite active material obtained by the preparation method.

[0054] In the present invention, the negative electrode material is a negative electrode without an external conductive agent, and may further be composed of a negative electrode active material and a binder.

[0055] In the present invention, in the negative electrode material, the content of the negative electrode active material is 80-95wt.%.

[0056] The present invention also provides an alkali metal battery, which comprises the negative electrode of the present invention.

[0057] The alkali metal battery of the present invention may be, for example, a sodium ion battery or a lithium ion battery.

[0058] The alkali metal battery of the present invention, in addition to containing the regenerated graphite active material of the present invention in the negative electrode, also selectively contains the characteristic of no conductive agent, and other components and parts can be conventional.

[0059] Beneficial Effects

[0060] The present invention innovatively subjects the waste graphite to the gas and liquid two-stage treatment in advance, and further coordinates the atmosphere in the gas-solid treatment stage, the solute components in the liquid phase treatment stage, and the combination of negative pressure heat treatment and cold quenching process assisted by additives. This can improve the purification effect of graphite, and obtain high-purity regenerated graphite materials with excellent performance. For example, the regenerated graphite material described in the present invention can be assembled without the assistance of a conductive agent to obtain a battery with excellent first efficiency, fast charging, and long cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is the SEM image of the raw material of Example 1;

[0062] Figure 2 is the SEM image of the product of Example 1;

[0063] Figure 3 The first charge and discharge curve (0.2C) of the sample obtained in Example 1;

[0064] Figure 4 The cycle diagram of the sample obtained in Example 1 at 6°C / room temperature; DETAILED DESCRIPTION

[0065] The specific steps of the present invention are described below by way of examples. It should be understood that these examples are only for illustrating the present invention and are not intended to limit the scope of the present invention in any way. Various processes and methods not described in detail in the present invention are conventional methods known in the art.

[0066] The method of the present invention can be applied to waste graphite from any source. In the following case, as a typical implementation, the waste graphite negative electrode material from waste batteries is obtained by conventional current collector stripping, and its graphitization degree can be 88±2%; the fixed carbon content is 93±2%.

[0067] Example 1

[0068] Step 1: Place the waste graphite powder in an atmosphere furnace and keep it in an atmosphere A (air) at a temperature of 450±10°C for 6 hours to obtain a first-stage material;

[0069] Step 2: Mix the first-stage material with solution A (which contains an aqueous solution of 0.2M hydrochloric acid (solute a) and 0.1M sodium ferrite (solute b)) at a liquid-solid ratio of 5ml / g, and then ultrasonicate for 0.5-1h under 200W ultrasound, then fill it into a high-pressure reactor (filling volume is 70-80%), and then heat it to 110°C (solvent thermal temperature) for 6h, and then separate the solid and liquid, dry the filter cake, and break it up; to obtain the second-stage material;

[0070] Step 3: Mix the asphalt, the additive (cobalt octacarbonyl) and the second-stage material in a weight ratio of 10:1:100 to obtain a mixture, and then keep it at a negative pressure of less than 50 Pa and a temperature of T1 (1200±50°C) for 6 hours, then cool it to T2 (450±50°C) with the furnace and mix it with liquid nitrogen (cooling medium) for cold quenching to obtain the regenerated graphite active material.

[0071] Example 2

[0072] Compared with Example 1, the only difference is that the conditions of step 1 are changed, and the experimental groups are:

[0073] Group A: Change the type of atmosphere A to 15% oxygen + 5% ammonia, with the balance being nitrogen;

[0074] Group B: Change the temperature of step 1 to 400±10℃ and keep it for 8h;

[0075] Other operations and parameters are the same as in Example 1.

[0076] Example 3

[0077] Compared with Example 1, the only difference is that the conditions of step 2 are changed. The experimental groups are:

[0078] Group A: Solution A was changed to 1M nitric acid and 0.5M potassium ferrite; the solvothermal temperature was 130°C and the holding time was 5h;

[0079] Group B: 8% of the weight of sodium ferrite in ferric acetate was added to the solute b, and the concentration of the solute b in the solution was the same as that in Example 1;

[0080] Group C: ethanol was added to solvent A, where the volume ratio of ethanol to water in solution A was 0.1:1;

[0081] Other operations and parameters are the same as in Example 1.

[0082] Example 4

[0083] Compared with Example 1, the only difference is that the conditions in step 3 are changed. The experimental groups are:

[0084] Group A: The auxiliary agent is nickel acetate;

[0085] Group B: The auxiliary agent is a mixture of dicobalt octacarbonyl and nickel acetate, with a mass ratio of 1:1; the amount of the total auxiliary agent is the same as that in Example 1;

[0086] Group C: Asphalt, additives, and second-stage material are in a weight ratio of 8:2:100. The temperature of T1 is 1050±50℃, and the insulation time is 10h; the temperature of T2 is 500±50℃, and the cooling medium is dry ice.

[0087] Group D: Asphalt, additives, and second-stage material were slurried with ethanol (liquid-to-solid ratio was 2 ml / g), and stirred at a pressure of 5 atm for 1 h, and then evaporated to remove the solvent to obtain a mixture, which was then subjected to subsequent negative pressure heat treatment and cold quenching treatment;

[0088] Group E: After keeping at temperature T1, it was cooled to temperature T2 using carbon dioxide atmosphere;

[0089] Other operations and parameters are the same as in Example 1.

[0090] Comparative Example 1

[0091] Compared with Example 1, the only difference is that in step 1, the atmosphere A is Ar, and the other operations and parameters are the same as Example 1.

[0092] Comparative Example 2

[0093] Compared with Example 1, the only difference is that, in step 2, in solution A, potassium permanganate is used in an equimolar amount to replace the sodium ferrite, and other operations and parameters are the same as in Example 1.

[0094] Comparative Example 3

[0095] Compared with Example 1, the only difference is that in step 2, the temperature of the treatment stage is controlled to be 60° C. Other operations and parameters are the same as in Example 1.

[0096] Comparative Example 4

[0097] Compared with Example 1, the only difference is that the waste graphite powder is first used as the raw material for the treatment of step 2, the obtained product is used as the raw material for the treatment of step 1, and then the obtained material is subjected to step 3 and subsequent treatments. Other operations and conditions are the same as in Example 1.

[0098] Comparative Example 5

[0099] Compared with Example 1, the only difference is that in step 3, sodium chloride or the like is used to replace the auxiliary agent by weight, and other operations and parameters are the same as in Example 1.

[0100] Comparative Example 6

[0101] Compared with Example 1, the only difference is that in step 3, no cold quenching treatment is performed, and furnace cooling is directly performed. Other operations and parameters are the same as in Example 1.

[0102] Electrochemical performance test method:

[0103] The regenerated graphite negative electrode active material and binder (LA-133, CMC) prepared in each case were uniformly mixed in a mass ratio of 96:4, and then deionized water was added to make a uniform slurry, which was coated on a copper foil and placed at 120°C for vacuum drying for 12 hours to obtain a regenerated graphite negative electrode sheet without a conductive agent.

[0104] A CR2032 button battery shell was used, the obtained regenerated graphite negative electrode sheet was used as the working electrode, the metal lithium sheet was used as the counter electrode, a Celgard 2400 type diaphragm was used, nickel foam was used as the counter electrode side current collector, and a solution of ethylene carbonate + dimethyl carbonate + diethyl carbonate (EC+DMC+DEC, 1:1:1) containing 1M LiPF6 was used as the electrolyte. The cells were assembled in a glove box under an argon atmosphere, and then compressed and packaged using a sealing machine to obtain a button lithium battery.

[0105] The battery cycle performance was tested at room temperature, with a test voltage range of 0.01V to 1.5V and a test rate of 0.2C and 6C. The results are shown in Table 1 and Table 2:

[0106] Table 1:

[0107]

[0108]

[0109] Table 2

[0110]

[0111] By comparing Table 1 with Table 2, the present invention uses the process described in the present invention to optimize the physical and chemical characteristics of the regenerated graphite, and to improve its rate and long cycle effect at a high rate.

[0112] In addition, compared with Example 1 and Example 2, the composite functional gas of oxygen-ammonia can obtain a better regenerated graphite rate and high rate stability. It can be seen from Examples 1 and 3 that a better technical synergistic effect can be obtained by combining sodium ferrite and ferric acetate. It can be seen from Examples 1 and 4 that a better technical synergistic performance can be obtained by using an additive containing dicobalt octacarbonyl, and / or pressurized compounding and carbon dioxide gas cooling treatment.

Claims

1. A method for preparing a regenerated graphite active material, characterized in that the steps include: Step (1): Gas and liquid two-stage processing The waste graphite powder is subjected to a first-stage gas-solid treatment in atmosphere A in advance to obtain a first-stage material; The first-stage material is then placed in an aqueous solution containing solute a and solute b for a second stage of solvothermal treatment to separate and obtain two-stage materials; The atmosphere A contains at least one functional gas selected from oxygen, carbon dioxide and ammonia; the temperature of the first gas-solid treatment is 350-600°C; Solute a is the solute that can ionize into H + The solute b comprises ferrite; Step (2): The second-stage material, the additive and the carbon source are mixed and subjected to negative pressure heat treatment at temperature T1, and then cooled to temperature T2 and directly contacted with a cooling medium for cold quenching to obtain the regenerated graphite active material; The auxiliary agent is one or more of cobalt acetylacetonate, nickel acetylacetonate, cobalt naphthenate, nickel naphthenate, cobalt acetate, nickel acetate, dicobalt octacarbonyl, cobalt oxalate, nickel oxalate, and nickel benzoate; The temperature T1 is above 700°C, and the temperature T2 is between 300 and 600°C.

2. The method for preparing the regenerated graphite active material according to claim 1, characterized in that: The waste graphite powder is waste batteries, waste graphite crucibles, waste graphite electrodes, and waste graphite generated by the semi-conductive industry and the smelting industry; Preferably, the graphitization degree of the waste graphite powder is above 82%, and the fixed carbon content is above 80%.

3. The method for preparing the regenerated graphite active material according to claim 1, characterized in that: The functional gas in the atmosphere A is oxygen, and its content is 10-40v%; the functional gas is carbon dioxide, and its content is 5-20v%; the functional gas is ammonia, and its content is 2-8v%; Preferably, in the atmosphere A, the functional gas is a mixture of oxygen and ammonia in a volume ratio of 1 to 5:1; Preferably, the atmosphere A also allows the presence of diluent gas; Preferably, the time for the first gas-solid treatment is 4 to 12 hours.

4. The method for preparing the regenerated graphite active material according to claim 1, characterized in that: The solute a includes one or more of hydrochloric acid, sulfuric acid, and nitric acid; Preferably, in the solute b, the ferrite includes at least one of sodium ferrite, potassium ferrate, potassium ferrate and zinc ferrite; Preferably, the solute b further comprises at least one auxiliary solute b1 selected from the group consisting of ammonium ferric citrate, ammonium ferric sulfate and ferric acetate; Preferably, in the solute b, the solute b1 is 1 to 15% by weight of the ferrite; Preferably, in the aqueous solution, the concentration of the solute a is 0.1 to 2 M; the concentration of the solute b is 0.1 to 2 M; Preferably, the aqueous solution may contain a water-soluble organic solvent; more preferably, at least one of methanol, ethanol, acetone, isopropanol, n-propanol and acetic acid; Preferably, the first-stage material and the aqueous solution are pre-ultrasonicated and then placed in a closed container and heated for the second-stage solvent thermal treatment; Preferably, the temperature of the second stage solvent thermal treatment is above 100°C, further 100-150°C; Preferably, the second stage of solvent thermal treatment lasts for 4 to 12 hours.

5. The method for preparing the regenerated graphite active material according to claim 1, characterized in that: The auxiliary agent comprises dicobalt octacarbonyl, and selectively comprises one or more of nickel acetylacetonate, nickel naphthenate, nickel acetate, nickel oxalate, and nickel benzoate; Preferably, the weight ratio of the second-stage material to the additive is 100:0.2-5; Preferably, the carbon source comprises one or more of asphalt, polypropylene, phenolic resin, starch, ethylenediamine, and polyethylene glycol; Preferably, the weight ratio of the second stage material to the carbon source is 100:5-15; Preferably, the second-stage material, the additive, and the carbon source are mixed under liquid phase positive pressure, and then subjected to a desolventizing treatment to obtain a mixture, and then the obtained mixture is subjected to a subsequent negative pressure heat treatment; Preferably, the pressure in the positive pressure mixing stage is above 5 atm; Preferably, after the negative pressure heat treatment is completed, the atmosphere B is used to assist cooling to a temperature T2; Preferably, the atmosphere B includes one or more of nitrogen, argon, helium and carbon dioxide.

6. The method for preparing the regenerated graphite active material according to claim 1, characterized in that: The cooling medium is liquid nitrogen, dry ice or water.

7. A regenerated graphite active material obtained by the preparation method according to any one of claims 1 to 6.

8. An application of the regenerated graphite active material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: It is used as negative electrode active material to prepare alkali metal ion batteries; Preferably, the negative electrode active material and the binder are combined to prepare a negative electrode material without an external conductive agent, and the negative electrode material is used for preparing an alkali metal ion battery.

9. A negative electrode of an alkali metal battery, comprising a negative electrode current collector and a negative electrode material composited on the surface thereof, wherein the negative electrode material comprises a negative electrode active material and a binder, wherein: The negative electrode active material comprises a regenerated graphite active material obtained by the preparation method according to any one of claims 1 to 6; Preferably, the negative electrode material consists of a negative electrode active material and a binder; Preferably, in the negative electrode material, the content of the negative electrode active material is 80 to 95 wt.%.

10. An alkali metal battery, characterized in that: The negative electrode according to claim 9 is included.

Citation Information

Patent Citations

  • High-rate regenerated graphite negative electrode material as well as preparation method and application thereof

    CN118198570A

  • Carbon-coated graphite material taking waste batteries as raw materials and preparation method of carbon-coated graphite material

    CN118486939A

  • Porous carbon, composite material, diaphragm modification material and application

    CN116040627A

  • Negative electrode material demagnetizing method, pole piece, energy storage device and electric equipment

    CN116443950A

  • Preparation method of PP-based lithium-supplementing diaphragm and cathode-free lithium ion battery

    CN116565448A

Cited By

  • Waste graphite regenerated material as well as preparation and application thereof

    CN120097336A